2005
DOI: 10.1088/0264-9381/22/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Curvature properties of four-dimensional Walker metrics

Abstract: A Walker n-manifold is a semi-Riemannian manifold, which admits a field of parallel null r-planes, with . In the present paper we study curvature properties of a Walker 4-manifold (M, g) which admits a field of parallel null 2-planes. The metric g is necessarily of neutral signature (+ + − −). Such a Walker 4-manifold is the lowest dimensional example not of Lorentz type. There are three functions of coordinates which define a Walker metric. Some recent work shows that a Walker 4-manifold of restricted type wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The fact that all known examples of nonsymmetric Jordan-Osserman metrics had nilpotent Jacobi operators of degree two or three suggested that no other examples could exist (cf. [7], [12], [16]). However, very recently the authors have shown the existence of a family of Type II Jordan-Osserman metrics with non-nilpotent Jacobi operators [10].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that all known examples of nonsymmetric Jordan-Osserman metrics had nilpotent Jacobi operators of degree two or three suggested that no other examples could exist (cf. [7], [12], [16]). However, very recently the authors have shown the existence of a family of Type II Jordan-Osserman metrics with non-nilpotent Jacobi operators [10].…”
Section: Introductionmentioning
confidence: 99%
“…In [3], Einsteinian, Osserman or locally conformally flat Walker manifolds were investigated in the restricted form of metrics when c(u 1 , u 2 , u 3 , u 4 ) = 0. In this paper, following [3], we consider the specific Walker metrics on a 4-dimensional manifold with…”
Section: The Canonical Form Of a Walker Metricmentioning
confidence: 99%
“…Among these, the significant Walker manifolds are examples of the non-symmetric and non-homogeneous Osserman manifolds [2,3]. Recently, it was shown [4,6,7] that the Walker 4-manifolds of neutral signature admit a pair comprising an almost complex structure and an opposite almost complex structure, and that Petean's nonflat indefinite Kahler-Einstein metric on a torus was obtained as an example of a Walker 4-manifold.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of Walker manifolds with g 34 = 0 has been studied in [11]. We impose a different condition by setting g 33 = g 44 = 0 so the non-zero components of the metric are given by:…”
Section: Walker Geometrymentioning
confidence: 99%